Theoretical and Computational Basis for CATNETS - Annual Report Year 2 - Torsten Eymann; Werner Streitberger; Daniel Veit; Georg Buss; Björn Schnizler; Dirk Neumann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2006)
In this work the self-organising potential of the CATNETS allocation mechanism is described to provide a more comprehensive view on the research done in this project. The formal description of either the centralised and decentralised approach is presented. Furthermore the agents' bidding model is described and a comprehensive overview on how the catallactic mechanism is incorporated into the middleware and simulator environments is given.
urn:nbn:de:bvb:703-opus-3639
Keywords: 330; Decentralized Market Mechanisms; Centralized Market Mechanisms; Catallaxy; Market Engineering; Simulator Integration; Prototype Integration